(untitled) (Bangladesh Journal of Medicine, 2023)
Bangladesh is one of the most densely populated areas in the world. Renal diseases are increasingly recognized and encompasses a large share of the health sector. About 20 million people are suffering from chronic kidney disease, and of them, approximately 35,000–40,000 develop endstage renal disease each year. Chronic glomerulonephritis, diabetes mellitus and hypertension are the principal causes of chronic kidney disease. Hypovolemia, sepsis, obstetric complications and drugs (including herbal and homeopathic remedies) are common causes of acute kidney injury. All three renal replacement therapy modalities (hemodialysis, peritoneal dialysis and renal transplantation) are performed in Bangladesh, yet only 25% of end-stage renal disease patients have access to treatment due to inadequate facilities and high healthcare costs. Nephrology as a specialty started its journey in 1973 in Bangladesh and now about 300 Nephrologists are managing the subject. Still there is huge need for more Nephrologists, as only one nephrologist is available for about every 0.8 million people. The country has improved financially from low- to low-middleincome country. Health sector is also more improving gradually. The government is now setting up renal care at rural level, introducing screening programs for early detection and prevention of kidney and other noncommunicable diseases. At the same time steps are under way to improve the advanced renal services at secondary and tertiary health institutes. Kidney transplantation started in 1982 and only live related transplantation are being done in several government and private organization. ABO-incompatible kidney transplantation has already been performed. Recently decease renal transplantation has also been performed. Research and training opportunities are expanding in collaboration with international organizations. Renal services appears up to date in this country but needs more and more enhancement to cope up the ever increasing burden. Bangladesh J Medicine 2023; 34(3): 180-185